International positioning of South African electricity prices and commodity differentiated pricing - Thopil, George A.; Pouris, Anastassios (South African Journal of Science, 2013)
The South African electricity industry has seen a dramatic increase in prices over the past 3 years. This increase has been blanketed across all sectors and is based on a number of factors such as sector, usage and, in the case of domestic pricing, suburb. The cost of electricity in South Africa, particularly to the industrial sector, has been among the lowest in the world. In this paper, we analyse the recent price increases in the South African electricity sector and discuss the price determination mechanism employed by Eskom, South Africa’s electricity provider. We also analyse the revenue and sales of Eskom and review the electricity price from an international perspective. The concept of differential pricing and international benchmarking is analysed as a possibility for the South African industrial electricity industry, so that all sectors are not adversely affected by across-the-board increases. Our aim is to raise the question of whether South Africa’s electricity prices are in line with international increases and to suggest the possibility of differentiated prices in the local electricity sector.